Discussion on Item Teaching of Power Switch - Ma, Hanwen (Journal of Theory and Practice of Contemporary Education, 2023)
The switch power supply technology course is the main core course of the electrical engineering specialty. This course comprehensively uses the analog electronic technology, automatic control principle, power electronic technology, electromagnetic field and simulation technology and other course knowledge learned in the early stage to carry out the switch power supply circuit and system design course. It is an important professional practice course of the electrical specialty. This course is very practical, and it is also a course that can comprehensively improve students' practical ability. In the teaching of electronic technology, some of our teachers often neglect the content of switching power supply, which is not in line with the current production and life reality. This paper briefly analyzes the project teaching of power switch.